Building resilience through locally led climate action: The significance of Kenya’s participatory scenario planning - Kiogora, Joseline; Ghosh, Aniruddha; Murage, Paul; Gamoyo, Majambo; Wahome, Anastasia; Ogutu, Liz; Sande, Stephen; Koech, Grace; Chemutt, Joseph; Sotelo, Steven; Navarro, Carlos (2024)
Participatory Scenario Planning (PSP) workshops - facilitated by the Alliance of Bioversity International and CIAT, in collaboration with the International Livestock Research Institute - were conducted in nine counties in Kenya during the release of the national forecast for March, April, and May (MAM) rains by the Kenya Meteorological Department. The objective was to address climate challenges by integrating meteorological insights with local knowledge, convening stakeholders for collaborative discussions, and developing tailored advisories. These efforts aimed to translate high-level climate data into actionable strategies for communities, fostering climate resilience.